Methodological Issues of Studying the Development of Craftsmanship During the Emir Timur Era in Foreign Sources in the XVI-XX Centuries (Zien Journal of Social Sciences and Humanities, 2022)
The role of Emir Temur as the head of state in the economic development of the Sultan, especially in the economic policy of the craftsmanship, has not been studied by economists as a single topic. Nevertheless, in this regard, the leading foreign writers and scholars in the social sciences have mentioned in their works. This article analyzes the studies associated with the Emir Temur era in the 18th and 20th centuries